A COMPLEXIDADE ENVOLVIDA NA PRÁTICA DA EDUCAÇÃO AMBIENTAL PELOS PROFESSORES NO CONTEXTO ESCOLAR - Santos, Daniela de Almeida dos (2019)
Environmental Education (EA) is one of the most important alternatives for facing the social and environmental crisis and the school is one of the most important spaces for its development. The National Curriculum Guidelines for Environmental Education, recommends that EA be worked on in all curricula of different levels and modalities of education. On the other hand, countless researches have pointed to the predominance of conservative approaches in their formal insertion. Thus, the present research aims to analyze the complexity involved in the insertion of EE in the school context, especially emphasizing the curriculum, the initial formation and the teacher's practice. The research is qualitative approach having as participants of the research teachers from a State College of a city of Paraná's State, who answered a questionnaire and participated in a focus group. Another instrument used was the document analysis, which had as its object of investigation the curricula of the undergraduate courses of the research participants, before and after the implementation of the National Curriculum Guidelines for Environmental Education. The curricula were analyzed based on Curriculum Environmental indicators. The results revealed that teachers started and practice EE, but many reports approached of Conservative and Pragmatic approaches. About the teachers initial formation reported few experiences related to EE during the undergraduate, in some reports it was realized that it was worked in a secondary way as separate projects and sporadically. The curricula revealed that prior to 2012 the EA was not included in these documents, or simply cited it in the text without showing the approach used. The curriculum of 2018 shows a breakthrough in relation to the EA, but they still needs theoretical and methodological support.